On the move to meaningful internet systems : OTM 2017 Workshops : Confederated International Workshops, EI2N, FBM, ICSP, Meta4eS, OTMA 2017 and ODBASE Posters 2017, Rhodes, Greece, October 23-28, 2017, Revised Selected Papers /: OTM 2017 Workshops : Confederated International Workshops, EI2N, FBM, ICSP, Meta4eS, OTMA 2017 and ODBASE Posters 2017, Rhodes, Greece, October 23-28, 2017, Revised Selected Papers. (2018) - Unknown
No abstract available